Importance of second and third generation ELISA test in detection of HVC antibody - Sedat BOYACIOĞLU; Münire TURAN; Gürden GÜR; Mete ÖZDOĞAN; Orhan ÖZGÜR; Hasan TELATAR (Turkish Journal of Gastroenterology, 2019)
-